Effect of superficial cervical plexus nerve block with Ropivacaine or a combination of different adjuvants on perioperative analgesia and quality of postoperative recovery in patients undergoing radical thyroid cancer surgery under general anesthesia: a prospective randomized controlled trial - Xiaoyu Kang; Caifen Li; Liuyu Lu; Xiaotong Qin; Yonghao Wang; Yang Lu; Li Ma; Shaoliang Zhu; Zheng Gong (World Journal of Surgical Oncology)
Abstract Objective To investigate the effect of ultrasound-guided bilateral superficial cervical plexus nerve blocks with Ropivacaine or a combination of different adjuvants on perioperative analgesia and quality of postoperative recovery in patients undergoing radical thyroid cancer surgery under general anesthesia with nerve monitoring without muscarinic maintenance. Methods A total of 140 patients undergoing elective radical thyroid cancer surgery were randomly divided into four groups, with 35 cases in each group: general anesthesia alone group (Group C), general anesthesia + Ropivacaine group (Group R), general anesthesia + Ropivacaine combined with dexmedetomidine group (Group R1), and general anesthesia + Ropivacaine combined with dexamethasone group (Group R2). The primary observation index were postoperative resting and active Visual Analogue Score. The secondary observation index were hemodynamics, intraoperative sedative and analgesic medication use, postoperative analgesic requirements, postoperative recovery indicators, Richards-Campbell Sleep Questionnaire scores, Quality of Postoperative Recovery-15 scores, and adverse reactions. Results Compared with group C, the resting and active VAS scores in group R were lower within 12 h after surgery (P < 0.05), the resting and active VAS scores in groups R1 and R2 were lower within 24 h after surgery (P < 0.05). Compared with group R, the VAS scores of patients in groups R1 and R2 were lower within 6 to 24 h after operation (P < 0.05). Compared with group R2, only the sedation score after extubation was higher in R1 group (P < 0.05), and there was no statistical difference in any other aspects (P < 0.05). Conclusion Bilateral superficial cervical plexus nerve blocks with Ropivacaine or a combination of different adjuvants are superior to general anesthesia alone in terms of intraoperative hemodynamics, the amount of sedative and analgesic drugs, and analgesic efficacy and quality of recovery in patients undergoing radical thyroid cancer surgery with nerve monitoring without muscarinic maintenance. Ropivacaine combined with an adjuvant has better analgesic effectiveness and quality of recovery than without an adjuvant, and Ropivacaine combined with dexmedetomidine has a better sedation level than dexamethasone.